2020
DOI: 10.18820/2519593x/pie.v38i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Kenyan Doctoral Students’ Success: Roles of Motivation and Self-Efficacy

Abstract: Doctor of philosophy (PhD) degree holders are highly regarded in Kenya, especially in academia, and the Kenyan economy needs them to undertake administrative, research and innovation roles in academia and industry. However, attaining this qualification is arduous and Kenyan PhD programmes are characterised by low enrolment numbers, long degree completion times and low graduation rates. In other countries, PhD students' success has been linked to motivation and self-efficacy. This cross-sectional study explores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…On the contrary, McBrayer et al (2018) found high self-efficacy scores among doctoral students, but did not find a correlation between self-efficacy and time to degree completion warranting further research. Thus, it is important to note, current research has shown a potential explanation of high self-efficacy scores may be indicative of overconfidence as leaders by nature may exhibit confidence in their capabilities due to their chosen leadership field (Matheka et al, 2020). Additionally, researchers have cautioned there are existing problems with differentiating the effects of self-efficacy and other constructs, such as self-concept, expectancy value, student demographics, as well as measures of personal, psychosocial, and institutional factors (Gardner, 2010).…”
Section: Theoretical Framework: General Self-efficacymentioning
confidence: 90%
“…On the contrary, McBrayer et al (2018) found high self-efficacy scores among doctoral students, but did not find a correlation between self-efficacy and time to degree completion warranting further research. Thus, it is important to note, current research has shown a potential explanation of high self-efficacy scores may be indicative of overconfidence as leaders by nature may exhibit confidence in their capabilities due to their chosen leadership field (Matheka et al, 2020). Additionally, researchers have cautioned there are existing problems with differentiating the effects of self-efficacy and other constructs, such as self-concept, expectancy value, student demographics, as well as measures of personal, psychosocial, and institutional factors (Gardner, 2010).…”
Section: Theoretical Framework: General Self-efficacymentioning
confidence: 90%
“…In 2015, Kenya’s public universities produced 390 PhD graduates an increase from 205 in 2012 (Commission for University Education, 2016). Several reasons have been claimed to explain these PhD low graduate rates, including challenges of student’s life and work balance, funding constraints, lack of research facilities and equipment, and shortages of qualified supervisors (Barasa & Omulanda, 2018, Matheka et al, 2020).…”
Section: Methodology and The Available Datamentioning
confidence: 99%
“…Unlike other personal resources, the intrinsic motivation is a significant internal resource of doctoral students that has been witnessed in literature. Intrinsic motivation is the internal desire to study, that is critical in achieving program completion (Dericks et al, 2019;Matheka et al, 2020). Intrinsic motivation of the doctoral student is often associated with their positive personal experience and its influence on improving their performance and academic engagement (Litalien & Guay, 2015).…”
Section: Intrinsic Motivation As a Personal Resource In The Doctoral ...mentioning
confidence: 99%
“…Intrinsic motivation limits the influence of hindrance demands on the strain and, in turn, improves the mental health of the doctoral student (McCauley & Hinojosa, 2020). Intrinsically motivated doctoral students undertake doctoral education due to their inherent interest in acquiring knowledge in their domain area and are capable of withstanding hindrance demands (Matheka et al, 2020). Intrinsic motivation with contextual resources supports doctoral learning outcomes and reduces the effect of burnout (van den Broeck et al, 2011).…”
Section: Intrinsic Motivation As a Personal Resource In The Doctoral ...mentioning
confidence: 99%
See 1 more Smart Citation